1997
DOI: 10.2134/jeq1997.00472425002600010027x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient, Carbon, and Mass Loss during Composting of Beef Cattle Feedlot Manure

Abstract: Quantification of nutrient and mass loss during composting is needed to understand the composting process, to implement methods for nutrient conservation, and to reduce potential adverse environmental impact. Beef cattle feedlot manure was composted in a windrow on an open concrete area in 1992, 1993, and 1994 to determine the amounts of nutrient, C, and mass loss during composting. The area was enclosed on all sides with a 0.2 m high metal sheet to direct runoff to a fiberglass tank (4000 L) during rainfall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
1
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(183 citation statements)
references
References 3 publications
16
152
1
9
Order By: Relevance
“…By the end of the 2004 season in Field B, however, the apparent N mineralization rate was positive, reflecting a net gain in buried bag inorganic N relative to total N applied in every amended treatment ( Table 9). The apparent N mineralization rate where composttreated was very low, reflecting compost's generally recalcitrant organic compounds (Eghball et al 1997). The apparent N mineralization rate of the Manure2 treatment, similar to that of Manure1, exceeded that of both compost treatments.…”
Section: Apparent N Mineralization Ratementioning
confidence: 90%
“…By the end of the 2004 season in Field B, however, the apparent N mineralization rate was positive, reflecting a net gain in buried bag inorganic N relative to total N applied in every amended treatment ( Table 9). The apparent N mineralization rate where composttreated was very low, reflecting compost's generally recalcitrant organic compounds (Eghball et al 1997). The apparent N mineralization rate of the Manure2 treatment, similar to that of Manure1, exceeded that of both compost treatments.…”
Section: Apparent N Mineralization Ratementioning
confidence: 90%
“…Composting should increase soluble salts as dry matter losses increase during composting and the salts become more concentrated in the final product. However, leaching and runoff losses from compost windrows can offset this concentration effect and result in lower soluble salts in the composted manure (Eghball et al 1997). Eghball et al (1997) reported in a 3-yr study that K, Na, Ca, and Mg were generally higher in composted than fresh beef cattle manure, and that EC was generally lower in composted manure or similar to fresh manure.…”
Section: Discussionmentioning
confidence: 99%
“…However, leaching and runoff losses from compost windrows can offset this concentration effect and result in lower soluble salts in the composted manure (Eghball et al 1997). Eghball et al (1997) reported in a 3-yr study that K, Na, Ca, and Mg were generally higher in composted than fresh beef cattle manure, and that EC was generally lower in composted manure or similar to fresh manure. We calculated the SAR and PAR from Eghball's data, and there was no trend in SAR, and the PAR was higher for composted than fresh manure in 2 of 3 yr. Larney et al (1999) reported that active composting of beef cattle manure for 99 d increased concentrations of Na, SO 4 , and Cl, reduced concentrations of Ca, Mg, and K, and EC values remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Although C and N losses during active (turned) manure composting have been documented (Eghball et al 1997;Michel et al 2004;Larney et al 2006a), they have not been generally compared with losses during passive composting. During the thermophilic phase, there were significantly higher C mass losses for the active treatment (77% of initial) than the passive treatment (45%) ( Table 3).…”
Section: And N Mass Balance Estimatesmentioning
confidence: 99%